ADAPTASI KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) BERBASIS KKNI : (Model MBKM Program Studi di Perguruan Tinggi Keagamaan Islam) - Agus Nurkholiq (Pergunu Jawa Barat, 2022)
Adaptation to the concept of the study program curriculum development model and the implementation of MBKM activity programs. The implementation of the activity program includes the design of the MBKM activity program, guidelines for implementing MBKM activities, and the conversion of credit transfer/credit recognition. The results of the study are in the form of a study curriculum development model by adapting MBKM policies including planning, learning processes, assessments, and learning evaluations. Services for fulfilling the period and burden of learning as student learning rights, namely; (1) Students are given the opportunity to take courses in their own study program, for a minimum of 84 credits which are core courses that are mandatory to support learning achievement and the profile of study program graduates, (2) students are given the opportunity to take courses in the study program others within the PTKIS concerned including in this case STAI Bhakti Persada Bandung, a maximum of 20 credits according to future needs, interests and talents of students and (3) Students are given the opportunity to gain learning experience in other universities and Non-PT through Business Internship activities , Student Exchange, Thematic Community Service Program, Social Service and Final Project. Maximum 40 Credits. Implementation of the MBKM curriculum through 5 programs, namely the Student Exchange Program, Introduction to the School Environment through the Remote Area Movers Teacher Program, Business Internships, Thematic Community Service Program